Convergent validity of the occupational therapy adult perceptual screening test with two other cognitive-perceptual tests in South Africa - Razemba, Fadzai (My University, 2014)
In previous research done, convergent validity was not established for OT-APST with two cognitive-perceptual tests. In this research, the DLOTCA and RPAB were used as reference tools to determine the convergent validity of the OT-APST using Spearman’s correlation. The aim was to ascertain whether the three tests when administered at the same time would yield the same result. This was a quantitative cross-sectional study that was mainly correlative and comparative in nature. Convenience sampling was used (n=32). The tools compared evaluate similar constructs and were expected to have strong correlations. This current research revealed that six subscales of the OT-APST had significant correlations with similar cognitive areas from the DLOTCA and the OT-APST subscales often correlated with an appropriate item from the RPAB. This study provides sufficient evidence of the convergent validity of the OT-APST when compared to the DLOTCA and RPAB. The OT-APST proved useful in identifying patients with visual perceptual problems in a population not standardised for.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, 28 August 2014
Keywords: Occupational Therapy; Stroke